Vila de Paranapiacaba, Alto da Serra: um patrimônio ambiental, tecnológico e arquitetônico - Minami, Issao (Pós. Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 1996)
The railways importance in São Paulo: the reasons and conditions for the appearence of the São Paulo Railway C. Ltd; Vila de Paranapiacaba, Alto da Serra: the formal and referential aspects, your development period from 1860 to 1946